The Level of Mental Health Literacy among Medical Students of Universitas Gadjah Mada: A Study Using Mental Health Literacy Questionnaire-Short Version for Adults (MHLq-SVa) - Auliaurrohman, Aufa; Widayanti, MPH., Apt., Ph.D., Anna Wahyuni (Academic Hospital Journal, 2025)
Background: mental health problem is general challenge for today’s and future generation. Prevalence improvement for this problem reveals the importance of early diagnostic in order to improve medication and treatment effectiveness. One of preventive action is by increasing mental health literacy (MHL) that can be measured by applying Mental Health Literacy Short Version for Adults (MHLq-SVa).Objective: To measure level of mental health literacy among medical students of Gadjah Mada University (UGM) also to reveal relation between sociodemographic toward level of literacy.Method: The study is descriptive quantitative with cross-sectional method. The questionnaire was distributed to 102 respondents which were active medical students at UGM with convenience sampling method. The data was analyzed descriptively and statistically by applying One-Way ANOVA dan Mann Whitney U.Result: Level of mental health literacy among medical students of Gadjah Mada University has median value of 72 and average score is 71.0±6.01 with score range of 52-80. The result stated that 56.9% of respondents have high mental health literacy. Results of statistical test showed that years of study and field of study significantly correlate with mental health literacy score with p value less than 0.001. Meanwhile the sociodemographic characteristics of sex (p=0.166), type of residence (p=0.871), monthly expense (p=0.306) and perceived health status (p=0.135) did not show statictically significant correlation with mental health literacy score.Conclusion: Mental health literacy level among medical students of Universitas Gadjah Mada was relatively high and there was correlation between mental health literacy score and years of study and field of study.